The epidemiology of inflammatory bowel disease: Clues to pathogenesis? - Borowitz, Stephen M. (Frontiers in Pediatrics, 2023)
Historically, inflammatory bowel disease (IBD) was most common in North America and Europe and more common with a north-south gradient. Over the past century, there has been a marked increase in IBD in general and in childhood IBD in particular and over the past 50 years IBD has spread into the developing world. The greatest risk factor of developing IBD is an affected family member. Concordance rates between dizygotic twins is ~ 4% and ~ 50% in monozygotic twins, and more than half of pairs are diagnosed within two years of each other. Nevertheless, most patients with IBD do not have an affected family member. More than 200 genes are associated with an increased risk for IBD, but most associations are weak with odds ratios between 1.2 and 2.0 suggesting the environment plays a role. IBD is more common in urban than rural regions and is associated with “good standards” of domestic hygiene during childhood. People who migrate from areas with a low incidence to areas with a high incidence of IBD have an increased risk of developing IBD and the younger they are when they migrate, the greater their risk of developing IBD. Moreover, people who migrate from regions with a high incidence to areas with a low incidence of IBD have a decreased risk of developing IBD. Together, these findings strongly suggest particular environmental exposures occurring early in life may trigger inflammatory bowel disease in genetically susceptible individuals. The key is figuring out what those exposures might be.